YTHDF2 Gene rs3738067 A>G Polymorphism Decreases Neuroblastoma Risk in Chinese Children: Evidence From an Eight-Center Case-Control Study - Zeng, Huijuan; Li, Meng; Liu, Jiabin; Zhu, Jinhong; Cheng, Jiwen; Li, Yong; Zhang, Jiao; Yang, Zhonghua; Li, Li; Zhou, Haixia; Li, Suhong; Xia, Huimin; et al. (Frontiers in Medicine, 2021)
Neuroblastoma is a primary malignancy mainly occurring in children. We have reported that polymorphisms of several N6-methyladenosine (m6A) RNA modification-related genes contributed to neuroblastoma risk in previous studies. YTHDF2, a “reader” of RNA m6A modification, is involved in cancer progression. Here, we estimated the association between a YTHDF2 gene rs3738067 A>G polymorphism and neuroblastoma susceptibility in 898 neuroblastoma patients and 1,734 healthy individuals from China. We found that the rs3738067 A>G could decrease neuroblastoma risk [AG vs. AA: adjusted odds ratio (OR) = 0.76, 95% confidence interval (CI) = 0.64–0.90, P = 0.002; AG/GG vs. AA: adjusted OR = 0.81, 95% CI = 0.69–0.95, P = 0.011). Besides, the rs3738067 AG/GG genotype was related to reduced neuroblastoma risk in the following subgroups: children aged 18 months and under, boys, patients with tumors originating from retroperitoneal, patients at clinical stage IV, and cases at clinical stages III plus IV. Importantly, false-positive report probability analysis proved our significant results worthy of close attention of. The expression quantitative trait locus analysis results revealed that the rs3738067 was associated with the expression of YTHDF2.